حقوق و واجبات الأكراد السياسية والقانونية في ظل مئوية سايكس بيكو - الطنازفتي, علي محمد علي (Sulaimani Journal for Humanities, 2018)
ABSTRACT This research shows the impact of prejudice to the Sykes-Picot agreement on the Kurdish nation which did not take into account the historical right to form a state made them use all legal and political means in order to reach the construction of state gather them; and it seems that the international changes in the fight against terrorism and regional Iranian expansion and the fragility of the military and the security of the Iraqi state and delays in converting the region's share of the annual budget; as well as sectarian exclusion within the Iraqi state sponsor and assist in achieving the historic aspiration for independence.